Analisa Komparatif Ukuran Desain Tangga Kebakaran Studi Kasus: Apartemen Gading Nias Residences - Afriliani, Adelia; Khaliq , Ibnul; Faridwadji, Agus; Poltak, Hendrik (Prosiding TAU SNARS-TEK Seminar Nasional Rekayasa dan Teknologi, 2024)
In the construction of vertical residences, appropriate architectural standards are very necessary, especially in terms of the safety of building occupants, because unexpected events such as earthquakes and fires can occur at any time, this must be a separate focus when designing a vertical residence, as is one of the facilities Building safety commonly used as an emergency route is a fire ladder. In designing fire stairs, of course, guidance is needed, one of which is DKI Gubernatorial Regulation number 72 of 2021. Assessing the quality of fire stairs design is very important in ensuring the safety of building occupants in the event of a fire. The aim of the research is to analyze the design dimensions of the fire stairs in the Gading Nias Residence Apartment building, North Jakarta. This research was conducted using a comparative analysis method by collecting data, analyzing, evaluating the results and drawing conclusions regarding the suitability of implementation of DKI Gubernatorial Regulation number 72 of 2021 and providing recommendations for improvements if necessary. Through a literature study and comparative analysis of fire stair design measures, this research provides a deeper understanding of effective design principles for overcoming fire hazards. The research steps were carried out by visiting and observing the location directly, then measuring the design of the fire stairs in the Gading Nias Residence apartment and comparing it with DKI Gubernatorial Regulation number 72 of 2021. The research limitation is on the application of fire ladder design dimensions Therefore, it is hoped that the results of this research can contribute to the evaluation of the design of fire stairs and in particular regarding the measurements to make the best fire ladder plan to increase the overall safety of vertical buildings.